これはぜひ覚えましょう
x³+y³+z³-3xyz
=(x+y+z)(x²+y²+z²-xy-yz-zx)
という因数分解です。

【証明】
x³+y³+z³-3xyz
=(x+y)(x²-xy+y²)+z³-3xyz
=(x+y){(x+y)²-3xy}+z³-3xyz
=(x+y)³-3xy(x+y)+z³-3xyz
=(x+y)³+z³-3xy(x+y+z)

A³+B³
=(A+B)(A²-AB+B²)
で、A=x+y、B=zと考えて、
={(x+y)+z}{(x+y)²-(x+y)z+z²}-3xy(x+y+z)
=(x+y+z){(x+y)²-(x+y)z+z²-3xy}
=(x+y+z)(x²+y²+z²-xy-yz-zx)


【別解】
a³+b³+c³-3abc
の因数分解について

まずは、
a³+b³=(a+b)³-3ab(a+b)
を使って

与式=(a+b)³-3ab(a+b)-3abc+c³
=(a+b)³-3ab(a+b+c)+c³
=(a+b)³+c³-3ab(a+b+c)

ここで
(a+b)³+c³の部分は、
x³+y³=(x+y)(x²-xy+y²)
を使って
x=a+b
y=c
とすると、
(a+b+c){(a+b)²-(a+b)c+c²}
になります。

与式=
=(a+b+c){(a+b)²-(a+b)c+c²}-3ab(a+b+c)
=(a+b+c){(a+b)²-(a+b)c+c²-3ab}
=(a+b+c)(a²+2ab+b²-ac-bc+c²-3ab)
=(a+b+c)(a²+b²+c²-ab-bc-ca)